(untitled) (American Journal of Life Science and Innovation, 2023)
The samall-toothed pellonula, Pellonula leonensis is ecologically and economically important. It is good source of protein to rural coastal and riverine communities because of its taste. Despite the economic significance, information on its biology are scarce. We evaluated the morphometric and meristic traits of the species from two water bodies in the Niger Delta Region. The population obtained from ISABA Creek, Delta State were significantly (P˂0.05) smaller in all the morphometric traits analysed relative to the population from New Calabar River with the exception of Pectoral Fin Length (PFL) and Pelvic Fin Length (PvFL). The range of total length, TL and weight respectively of 3.70-8.52cm (X ̅=5.14±0.034cm) and 0.20-3.40g (X ̅=0.75±0.022g) for ISABA Creek population and 6.5-9.80cm (X ̅=8.35±0.06cm) and 1.7-7.30 g (X ̅=3.84±0.083g) for New Calabar River population was observed. The range of meristic characters significantly differed between the two waters bodies (p<0.05). The observed intraspecies differences could be attributed to environmental variables, fishing pressure and genetic factors. This study reveals the need for developing conservation strategies and domestication programs for species distributed in different water system.